2018
DOI: 10.3389/fpsyg.2018.01427
|View full text |Cite
|
Sign up to set email alerts
|

The Pattern of Stability and Change in Parental Locus of Control Over 6 Years and Teacher Ratings of Child Behavior

Abstract: A previous study from our group showed that parents’ locus of control (LOC) obtained before the birth of their child was associated with the child’s behavior at school in School Years 3 (ages 7–8) and 6 (ages 10–11). Here we examine whether a change in parental LOC over the first 6 years of the child’s life was associated with differences in his or her behavior as rated by their teachers. As before, we use data from the Avon Longitudinal Study of Parents and Children (ALSPAC). A modified version of the adult N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
4
0
1
Order By: Relevance
“…If it does and the results of the present study are confirmed by others, then focusing on the LOC of parents becomes important. Previous studies have found that parental externality is associated with negative children's outcomes, but also that children's difficulties are reduced when parents become more internal (Nowicki et al, 2018a;Nowicki et al, 2018b). This suggests that time could be spent helping parents to become more appropriately internal.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…If it does and the results of the present study are confirmed by others, then focusing on the LOC of parents becomes important. Previous studies have found that parental externality is associated with negative children's outcomes, but also that children's difficulties are reduced when parents become more internal (Nowicki et al, 2018a;Nowicki et al, 2018b). This suggests that time could be spent helping parents to become more appropriately internal.…”
Section: Resultsmentioning
confidence: 96%
“…Though relatively few LOC studies have focused on parents and parenting, one consistent result has been found: externality in one or both parents has been associated with more negative outcomes in the children, whether the outcomes were measured in preschool (e.g., Estroff et al, 1994); preadolescent or adolescent participants (e.g., Freed & Tompson, 2011). While cause and effect are difficult to determine, we (Nowicki et al, 2018a) found that parents who became more external over a six-year period had children with a greater number of teacher-rated difficulties on the Strengths and Difficulties questionnaire (SDQ) (Goodman, 2001) than those who were external but became internal over time. Such a result suggests that parental changes in LOC may affect their children's behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Elkins et al (2017) found that long term difficulties rather than single events appeared to be associated with changes in LOC as measured by items from Pearlin and Schooler’s Mastery module. In addition, other research ( Nowicki et al, 2018b ) found that changes toward greater parent externality were associated with children having more teacher reported difficulties, while transitions to greater parent internality were characterized by fewer ones.…”
Section: Discussionmentioning
confidence: 92%
“…Oprócz środowiska szkolnego ważnym czynnikiem wpływającym na rozwój poczucia kontroli jest dom rodzinny, w tym postawy wychowawcze oraz cechy osobowości rodziców. Wskazuje się, że dzieci rodziców, którzy charakteryzują się wewnętrznym poczuciem kontroli, są również predysponowane do przejawiania wewnętrznego poczucia kontroli (Nowicki i in., 2017;Nowicki, Gregory, Ellis, Iles-Caven, Golding, 2018). Badania z udziałem młodszych adolescentów wykazały także, że postawa akceptacji i zainteresowanie sprawami dziecka sprzyjają kształtowaniu się u niego wewnętrznego poczucia kontroli (Morton, Mann, 1998).…”
Section: Poczucie Kontroli W Perspektywie Rozwojowejunclassified